On inception - Heidegger, Martin, 1889-1976 (Studies in Continental thought., 2023)
"On Inception is a translation of Martin Heidegger's Gesamtausgabe 70. This work belongs to the crucial period, before and during WWII, when Heidegger was at work on a series of treatises that begins with "Contributions to Philosophy" and includes "The Event" and "The History of Beyng." These works are difficult, even hermetic, but represent a crucial development in Heidegger's thinking. On Inception deepens the investigation underway in the other volumes of the series and provides a unique perspective on Heidegger's thinking of Being and of Event. Here, Heidegger asks, with a greater insistence than anywhere else in his work, what it might mean to think of being as event, and not as presence. Event cannot be thought without the sense of a beginning - an inception - and so, Heidegger insists, we must try to think of being as inception, as fundamentally inceptive. On Inception pursues rigorously the difficult and puzzling implications of this speculation. It does not merely extend work already undertaken but also opens doors onto wholly other pathways"--